The Relationship between the Quality of Post Christmas Care Services and the Satisfaction of Postpartum Mothers at the Limboto Health Center - Febrianti Sau; Ita Sulistiani; Rachmawaty D. Hunawa (Universitas Muhammadiyah Palu, 2026)
The postpartum period is a period of 42 days after childbirth which is marked by physical, psychological, and social changes in the mother. In this phase, mothers need optimal health services to prevent complications, support recovery and successful breastfeeding. This study aims to determine the relationship between the quality of Post Natal Care (PNC) services and the satisfaction of postpartum mothers at the Limboto Health Center. Quantitative research method with cross sectional design. The population of 213 postpartum mothers with a sample of 68 respondents was determined using the Slovin formula. Data collection was carried out through a questionnaire on the quality of PNC services and the satisfaction of postpartum mothers. Data analysis used Fisher's Exact Test and Spearman Correlation tests. The results showed that most of the respondents had the quality of PNC service in the category of 43 people (63.2%), 15 people (22.1%), and 10 people (14.7%) lacked. The satisfaction level of postpartum mothers was mostly satisfied with 37 people (54.4%), satisfied with 16 people (23.5%), and dissatisfied with 15 people (22.1%). The results of the Fisher's Exact Test obtained a value of p = 0.000 (p < 0.05) and a Spearman coefficient r = 0.672 (p = 0.000) which showed that there was a meaningful relationship with strong correlation strength and positive direction. It was concluded that most postpartum mothers assessed the quality of PNC services as adequate and felt quite satisfied. There is a strong and positive meaningful relationship between the quality of PNC services and the satisfaction of postpartum mothers at the Limboto Health Center. It is recommended that the Puskesmas improve the quality of PNC services so that the satisfaction of postpartum mothers increases.